Synthesis of Some Biologically Active Isoxazolines - Barot, V.M.; Patel, M.R.; Naik, H.B. (Asian Journal of Chemistry, 2010)
Various 2-hydroxychalcones have been condensed with hydroxylamine hydrochloride to yield isoxazolines. The compounds have been characterised by elemental analysis, IR and NMR spectra.